THE LINGUOCULTURAL CONNOTATIONS OF AMERICAN DIALECTS (American Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the linguocultural connotations of American English dialects based on variationist linguistics and sociolinguistics theories. Dialects are examined not only as regional variants of the language but also as reflections of social identity, stereotypes, and cultural values within society. The article thoroughly explores the phonetic, lexical, and grammatical features of dialects such as Southern American English, African American Vernacular English (AAVE), Appalachian English, New York City English, Chicano English, and others, focusing on their cultural connotations, including regional pride, ethnic solidarity, social stigmatization, and historical resilience. From a linguocultural perspective, the role of dialects in shaping identity and reflecting power dynamics in society is emphasized, drawing on seminal works like William Labov's sociolinguistic stratification studies. The study predicts the transformation of these connotations under the influence of globalization, digital media, and migration, highlighting issues of linguistic justice and cultural preservation. Drawing on Uzbek linguocultural theories, the article underscores the dialectical relationship between language and culture, offering comparative insights into multilingual identities.